Reading Proclus and the Book of Causes, Volume 3 : On Causes and the Noetic Triad - Calma, Dragos (Studies in Platonism, Neoplatonism, and the Platonic Tradition, 2022)
Reading Proclus and the Book of Causes , published in three volumes, is a fresh, comprehensive understanding of the history of Neoplatonism from the 9th to the 16th century. This third volume gathers contributions on key concepts of the Platonic tradition (Proclus, Plotinus, Porphyry or Sallustius) inherited and reinterpreted by Arabic (e.g. Avicenna, the Book of Causes), Byzantine (e.g. Maximus the Confessor, Ioane Petritsi) and Latin authors (e.g. Albert the Great, Thomas Aquinas, Berthold of Moosburg, Marsilio Ficino etc.). Two major themes are presently studied: causality (in respect to the One, the henads, the self-constituted substances and the first being) and the noetic triad (being-life-intellect).